(untitled) (Ustozlar uchun, 2026)
This study provides a comparative-functional analysis of particles in English and Uzbek, languages that belong to different linguistic families and structural types. The research explores the semantic and pragmatic functions of particles, emphasizing their use in English as elements of phrasal verbs and discourse markers, whereas in Uzbek they predominantly express modal and emotional meanings. The study further examines the syntactic distribution of particles and their role in conveying emphasis in discourse. The results contribute to comparative linguistics, translation studies, and foreign language teaching methodology.